KEPATUHAN MENEBUS RESEP ULANG PASIEN DIABETES MELITUS YANG DIUKUR DENGAN MEDICATION POSSESSION RATIO DI APOTEK - Erna Prihandiwati; Abdul Mahmud Yumassik; Riza Alfian; Rizka Rizka; Maria Ulfah; Leonov Rianto (Jurnal Insan Farmasi Indonesia, 2023)
Diabetes mellitus is a chronic and progressive disease characterized by elevated blood sugar levels and requires continuous treatment. Adherence refill prescription is one of the factors that determine the success of therapy. Adherence with refilling prescriptions can be measured by the Medication Possetion Ratio (MPR) method. The purpose of this study was to determine the description of adherence with refilling prescriptions (Refill Adherence) of diabetes mellitus patients at a pharmacy in Banjarmasin City. This research method is non-experimental which is observational. Data collection was carried out retrospectively. The sample used in this study was a prescription for diabetes mellitus patients who met the inclusion and exclusion criteria. The sample selection method used is total sampling. Measuring refill adherence was done using the MPR method. The research data obtained are displayed descriptively. The results showed that 56 patients (98.25%) were classified as non-adherent to refill Adherence, and only 1 patient (1.75%) complied to redeem prescriptions for 6 months.